SISTEM PENGUKUR PERUBAHAN TEKANAN DARAH MENGGUNAKAN OKSIMETER FOTO SEBAGAI KOMPONEN UNTUK MENDETEKSI STRES PADA MANUSIA - Lukas, Lukas; Joenarto, Prawibowo (Teknik dan Ilmu Komputer, 2013)
Stress has various effects on humanâs body. People are frequently unaware that they are suffering from stress. Stress detection system can be useful to identify common stress symptoms and to avoid the stress level increase.Â  One indicator of stress is changes in blood pressure. This project aims at examining blood pressure to detect stress level and at detecting stress by using fuzzy logic with bio-signal inputs. Based on Pulse Wave Transit Time and Diastolic Time, blood pressure can be measured using photoplethysmograph attached to the finger and electrocardiogram attached to the body.Â  The study shows that the blood pressure increase is an indicator of stress although the increase varies for each individual. The system allows stress detection based on the general data.Â Â Â Â  Keywords: PPG, blood pressure, pulse wave transit time, diastolic time, stress detection